Validity of a Chemistry Learning Module Based on Socio-Scientific Issues - Utami, Restu; Prodjosantoso, Anti Kolonial (Jurnal Pendidikan Kimia Indonesia, 2023)
This paper aims to determine the validity and eligibility percentage of socio-scientific issues-based chemistry learning module by material and media experts. The method used in this research was Research and Development (R&D) using the 4D model by  Thiagarajan. The module was validated by two material experts and two media experts. The instrument used to obtain the validation data was an expert assessment questionnaire. The data were analyzed using quantitative descriptive analysis techniques. The validation value by material experts was 57.5, and its eligibility can be categorized as ’very good’. The percentage of eligibility from the material expert assessment obtained was 89.84%. The validation value by media experts was 61.50, and its eligibility can be categorized as ’very good’. The percentage of eligibility from the media expert assessment obtained was 96.09%.